Copper diffusion barriers for multilevel interconnecting metalization scheme in microelectronics appplication - Kim, Jae Hyung. (2008)
As a main part of thermal stability studies , the atomic intermixing, new compound formation and phase transitions in the test structure were studied. Another aim of our experiments is to clarify the effect of different Cu deposition methods on the diffusion barrier performance.